Mechanisms structuring host-parasitoid communities in a global warming perspective - Thierry, Mélanie Jeanne (Jihočeská univerzita, 2021)
Ecological communities are composed of a multitude of interacting species, and the outcome of pairwise interactions depends on other co-occurring species within the community. With current global environmental changes, both abiotic and biotic environment are changing, affecting the structure and dynamics of communities. I used a series of laboratory experiments on a set of Drosophila species and their parasitic wasps to investigate the effects of biotic and abiotic factors on interactions and communities. I first compared the outcome of host-parasitoid interactions across community modules commonly found in host-parasitoid communities (i.e., pairwise interaction, exploitative competition, apparent competition, and both exploitative and apparent competition). I found generally higher host suppression with multiple parasitoid species, but species-specific effects for parasitoid performance. I then observed that warming impacts host communities through direct effects on species performance rather than altered competitive interactions and parasitism. Finally, I found that temperature strongly influences the effects of multiple parasitoids on host suppression across different parasitoid assemblages, suggesting a general pattern for the environmental dependence of trophic and non-trophic interactions. My thesis emphasizes the importance of considering environmental factors and different interaction types to better predict community dynamics in a rapidly changing world.
Mechanisms structuring host-parasitoid communities in a global warming perspective
Keywords: Climate change; temperature; host-parasite networks; multiple predator effects; interactions; Drosophila; Climate change; temperature; host-parasite networks; multiple predator effects; interactions; Drosophila